Apremilast Is Effective in Lichen Planus Mucosae-Associated Stenotic Esophagitis - Jürg Hafner; Christoph Gubler; Karin Kaufmann; Stephan Nobbe; Alexander A. Navarini; Lars E. French (Karger Publishers, 2016)
A 74-year-old woman with extensive lichen planus mucosae (LPM) developed stenotic esophagitis that was refractory to intravenous glucocorticosteroids. Esophageal dilatations to 14 mm width were repeatedly performed without any lasting effect. After introducing oral apremilast, she experienced complete clinical remission within the first 4 weeks of treatment. Control esophagoscopy confirmed a marked recovery of the esophageal mucosa with no recurrence of the former stenosis. Our observation is in line with the case series of Paul et al. [J Am Acad Dermatol 2013;68: 255-261] who first reported on the benefit of apremilast in patients with extensive LPM. Ideally, the effectiveness of apremilast in LPM should be studied in a randomized controlled trial.